Difference equations on R_*^+, of the form u_n+2=f(u_n+1)u_n+λ, λ>0, with applications to perturbations of dynamical systems - Bastien, Guy; Rogalski, Marc (Sarajevo Journal of Mathematics, 2024)
There is classical difference equation on R_*^+ equation*premequat u_n+2u_n=f(u_n+1), 1 equation* that is in particular applied to several symmetric special QRT-applications. We study perturbations of this equation (1) by equation*deuxequat u_n+2(u_n+λ)=f(u_n+1),4mm λ>0, 2 equation* showing general theorems of regarding permanence, convergence or divergence, and attraction of the fixed point. -.6cm